Application of the Project-Based Learning Model to Improve Students' Creative Thinking Skills on Thermodynamics Material - Putri Anggraeni; Andri Suherman; Yudi Guntara (JURNAL EKSAKTA PENDIDIKAN (JEP), 2023)
Creative thinking skills are high-level abilities that must be possessed by students in this globalization era. Creative thinking skills can be developed through learning that can involve students directly in the learning process. The Project-based learning model is a learning model that can involve students actively in the learning process. This study aims to determine the effect of the Project-Based Learning (PjBL) learning model to improve students' creative thinking skills on thermodynamics material. The population of this study was all XI IPA classes at SMAN 1 Pandeglang. The research sample was 30 students in class XI IPA 8 as the experimental class and 31 students in class XI IPA 1 as the control class. The research method used is a quantitative. This type of research is a quasi-experimental research design with a pretest-posttest nonequivalent control group design. The instruments used in this study were essay test questions with indicators of creative thinking ability, student response questionnaires, and observation sheets of learning implementation. The results of this study indicate an increase in learning outcomes (posttest) resulting in an N-gain calculation with a score of 0.62 for the experimental class which is higher than the score of 0.27 for the control class. With the help of the SPSS application version 26, it produces a prerequisite test that show the data is normally distributed and has the same/homogeneous variance. The results of the hypothesis test (t-test) using the Independent Sample T-Test test, the results show that there is an influence using the project-based learning (PjBL) model on students' creative thinking skills with a significance value of 0.000. This concludes that the project-based learning learning model can improve and influence students' creative thinking skills on thermodynamic material.